Ability to Work and Employment Rates in Human Immunodeficiency Virus (HIV)-1-Infected Individuals Receiving Combination Antiretroviral Therapy: The Swiss HIV Cohort Study. (1st February 2016) - Elzi, Luigia; Conen, Anna; Patzen, Annalea; Fehr, Jan; Cavassini, Matthias; Calmy, Alexandra; Schmid, Patrick; Bernasconi, Enos; Furrer, Hansjakob; Battegay, Manuel; ,; Barth, J.; et al.
Abstract: Background.  Limited data exist on human immunodeficiency virus (HIV)-infected individuals' ability to work after receiving combination antiretroviral therapy (cART). We aimed to investigate predictors of regaining full ability to work at 1 year after starting cART. Methods.  Antiretroviral-naive HIV-infected individuals <60 years who started cART from January 1998 through December 2012 within the framework of the Swiss HIV Cohort Study were analyzed. Inability to work was defined as a medical judgment of the patient's ability to work as 0%. Results.  Of 5800 subjects, 4382 (75.6%) were fully able to work, 471 (8.1%) able to work part time, and 947 (16.3%) were unable to work at baseline. Of the 947 patients unable to work, 439 (46.3%) were able to work either full time or part time at 1 year of treatment. Predictors of recovering full ability to work were non-white ethnicity (odds ratio [OR], 2.06; 95% confidence interval [CI], 1.20–3.54), higher education (OR, 4.03; 95% CI, 2.47–7.48), and achieving HIV-ribonucleic acid <50 copies/mL (OR, 1.83; 95% CI, 1.20–2.80). Older age (OR, 0.55; 95% CI, .42–.72, per 10 years older) and psychiatric disorders (OR, 0.24; 95% CI, .13–.47) were associated with lower odds of ability to work. Recovering full ability to work at 1 year increased from 24.0% in 1998–2001 to 41.2% in 2009–2012, but the employment rates did not increase. Conclusions.  Regaining full ability to work depends primarily on achieving viral suppression, absence of psychiatric comorbidity, and favorable psychosocial factors. The discrepancy between patients' ability to work and employment rates indicates barriers to reintegration of persons infected with HIV.